Research Study on Emotional Intellingence and Leadership Competencies Among Physicians - Mehmet KOCA; Zuhal YAPICI COŞKUN; Özlem COŞKUN; İrem BUDAKOĞLU (Forbes Tıp Dergisi, 2024)
Objective: In the current system, where there is an increasing burden of knowledge and complex health issues, along with complex tasks related to individual skills being insufficient alone in problem-solving, the formation of teams consisting of different areas of expertise and working together for the same purpose, sharing different responsibilities of the task, has become mandatory. A leader's essential quality is emotional intelligence. A leader should well understand themselves and the context they are in, and be able to direct, motivate, establish a communication network, and shape their environment. In medical education, programs are being enriched to ensure that future physicians, who will lead various teams, are aware of these qualities. Methods: Our study will shed light on the relationship between emotional intelligence and leadership from different perspectives and the current approach to the concept of leadership among physicians in our country, guiding areas to be developed in education. It is a descriptive cross-sectional study, where emotional intelligence and leadership scales were applied through a web-based socio-demographic form, and data analysis was conducted. Results: In the clinical leadership scale, no significant difference was found between the main branch groups (Surgery-Internal Medicine-Basic Medical Sciences) in terms of emotional intelligence scale scores according to one-way analysis of variance (p=0.329). A positive correlation of 0.465 was found between the Emotional Intelligence Scale and the Clinical Leadership Scale. Conclusion: An increase of one unit in the emotional intelligence scale affects the clinical leadership score by a factor of 0.46. A moderate relationship is observed.